Determination of Antibiotic Susceptibility of Avian Pathogenic Escherichia coli by Phenotypic and Genotypic Methods - Limbachiya, Bhargav B.; Mathakiya, Rafiyuddin A.; Patel, Krishna J.; Joddha, Harshrajsinh B. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
tEscherichia coli infection is one of the most important infections, which causes heavy economic losses in the poultry industry. It is caused by avian pathogenic E.coli (APEC), which belongs to the group Extra-intestinal Pathogenic E. coli (ExPEC). In this study, a total of 60 APEC isolates from various poultry farms located in and around Anand were evaluated for antibiotics susceptibility by disc diffusion (phenotypic) method for 21 different antibiotics. The E. coli isolates showed 100% resistance against pefloxacin, moxifloxacin and tetracycline followed by ampicillin (86.67%), levofloxacin (81.67%), amoxiclav and ciprofloxacin (71.67% each), co-trimoxazole (56.67%), sulphadiazine (53.34%) and erythromycin (33.33%). The study also revealed that E. coli isolates were highly susceptible to colistin (100.00%), followed by ceftriaxone and spectinomycin (85.00% each), cefixime (81.67%), amikacin (80.00%) and gentamicin (76.67%). All these isolates were also screened for the presence of 20 different antibiotic-resistant genes (ARGs) by genotypic method, i.e., polymerase chain reaction. PCR revealed presence of cmlA gene responsible for chloramphenicol resistance in cent percent isolates. The distribution of other ARGs in the E. coli isolates were qnrS (85.00%), aac(3)-IV (56.66%), strB (53.33%), aadA1 (51.66%), dhfrI (50.00%), tetB (41.66%) sulI and tetA (33.33% each), blaOXA (31.66%), cat1 and blaCMY (21.66% each), strA (6.67%), blaSHV (3.33%) and dhfrV (1.66%), while all the isolates were negative for blaTEM, ere(A), qnrA, qnrB and mcr-1 genes.
Keywords: Antibiotic-resistant genes (ARGs),; Avian Pathogenic E. coli; Genotypic method; Phenotypic method; Polymerase ChainReaction; Poultry industry